2019
DOI: 10.1093/ibd/izz258
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality in Crohn’s Disease Is Associated With Disease Activity and Risk for Hospitalization or Surgery

Abstract: Background and Aims Poor sleep quality in Crohn’s disease (CD) is associated with histologic activity and clinical relapse. We sought to characterize sleep dysfunction and determine the effect of poor sleep quality on risk for hospitalization and surgery. Methods Clinical data were collected for CD subjects including the Pittsburgh Sleep Quality Index (PSQI) and Harvey-Bradshaw index (HBI). The PSQI score and a brief medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…14 Another study found that poor sleep quality was associated with aggravated CD symptoms. 15 Differences in sleep duration between CD patients in exacerbation, remission and HC were also noted. 16 In addition, BDNF appears to be associated with inflammation.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…14 Another study found that poor sleep quality was associated with aggravated CD symptoms. 15 Differences in sleep duration between CD patients in exacerbation, remission and HC were also noted. 16 In addition, BDNF appears to be associated with inflammation.…”
mentioning
confidence: 91%
“…Sonnenberg et al showed that irregular working hours and exposure to artificial light are associated with the increased occurrence of IBD 14 . Another study found that poor sleep quality was associated with aggravated CD symptoms 15 . Differences in sleep duration between CD patients in exacerbation, remission and HC were also noted 16 …”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorder is one of the non-motor symptoms reported in PD patients in the prodromal phase (64,65). Interestingly, sleep disturbance has also been reported in IBD patients (66,67). The underlying mechanisms for the sleep disturbance in PD and IBD are yet to be elucidated.…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin (IL) -1, and IL-6 cause sleep disturbances, while sleep deprivation upregulates cytokines [97], particularly IL-1 and TNF-α. Clinical studies identified an association between sleep disturbances, disease activity, subclinical inflammation, and risk of IBD relapse [98][99][100]. A recent trial reported that poor sleep quality, evaluated using the Pittsburgh Sleep Quality Index, was associated to the absence of mucosal healing (P<0.05) [101].…”
Section: Inflammatory Intestinal Disorders and Celiac Diseasementioning
confidence: 99%